Narrative of Covids as Conspiracy on Youtube - Gemuh Surya Wahyudi; Awanis Akalili (Universitas Mataram, 2020)
Covid 19 pandemic which spread in Indonesia is not just science issue that shows a competition of scientist in developing theories and concepts to solve this problems. More important than science study, this issue also comes on the social study with some of naratives about conspiracy in media portals, one of them is YouTube. Using literature review method this research analyze what kind of narratives built by YouTube accounts that upload information about “Covid Conspiracy”. Analyze obtained from five YouTube accounts shows that Covid’s conspiracy narratives are built differently. From this paper, hopefully can describe audience are not just a consumers of media messages, but also media producers and how audience critical think and creativity create an information content about Covid conspirations on YouTube.